Tuberculosis burden in Korea compared with global trends, 1990–2021: a comparative ecological time-trend study. - Liu, Zhe; Park, Taesung (Journal of the Korean Medical Association / Taehan Uisa Hyophoe Chi, 2026)
Purpose: Tuberculosis (TB) remains a major public health concern in Korea. This study aimed to compare trends in TB burden between Korea and the global population from 1990 to 2021 using data from the Global Burden of Disease 2021 study. Methods: We analyzed TB incidence, prevalence, mortality, and disability-adjusted life years by age and sex. Joinpoint regression was used to estimate average annual percent changes in age-standardized rates. Age–period–cohort models were applied to disentangle age, period, and birth-cohort effects. Autoregressive integrated moving average (ARIMA) models were used to forecast age-standardized TB incidence and mortality through 2030. Results: The TB burden increasingly shifted toward older adults, with consistently higher rates observed in males in both Korea and globally. Joinpoint regression indicated that Korea experienced more rapid and consistent declines in TB burden compared with global trends. Age–period–cohort analyses showed that TB incidence and prevalence in Korea peaked in early adulthood and declined thereafter, with uniformly decreasing period and cohort effects from 1990 to 2021, whereas global patterns were less stable. ARIMA forecasts suggested that Korea's age-standardized incidence rate may approach very low levels by 2030, while global rates are expected to continue declining but remain substantial. Conclusion: Korea's TB control measures have outpaced global trends. To achieve TB elimination by 2030, sustained age- and sex-targeted interventions and strengthened public health strategies remain essential.